Possible Tacrolimus-associated seronegative Autoimmune Encephalitis presenting with subacute cognitive impairment and disorientation - case report - Hölzl, Konstantin; Albasini, Francesco (Frontiers in Medicine, 2025)
Autoimmune encephalitis (AE) is a multifaceted topic that encompasses various aetiologies and differential diagnoses. In certain instances, the patient’s serum or CSF may not reveal the presence of specific antibodies, which can leave healthcare providers unsure about the most appropriate course of treatment. This report outlines the case of a 71 years-old male who underwent a full-size liver transplantation and was subsequently maintained on Tacrolimus for immunosuppression. The patient presented with symptoms of confusion and decreased general orientation, which worsened over time. Following a thorough diagnostic workup, the patient was diagnosed with Antibody-negative Autoimmune Encephalitis (AE). He received treatment with high-dose steroids and Tacrolimus was later changed to Mycophenolate mofetil (MMF), which ameliorated his condition. This case highlights a potential link between long-term use of calcineurin inhibitors and seronegative AE. Hence, it may be advisable to consider Antibody-negative AE (ABnAE) as a potential diagnosis in patients under chronic immunosuppression who exhibit symptoms of sudden cognitive decline.